Self-learning and adaptive algorithms for business applications : a guide to adaptive neuro-fuzzy systems for fuzzy clustering under uncertainty conditions /: a guide to adaptive neuro-fuzzy systems for fuzzy clustering under uncertainty conditions. (2019) - Hu, Zhengbing; Bodyanskiy, Yevgeniy V; Tyshchenko, Oleksii K
No abstract available